2022
DOI: 10.1051/sicotj/2022016
|View full text |Cite
|
Sign up to set email alerts
|

Does meniscal repair impact muscle strength following ACL reconstruction?

Abstract: Purpose: Meniscal lesions are commonly associated with anterior cruciate ligament (ACL) rupture. Meniscal repair, when possible, is widely accepted as the standard of care. Despite advancements in surgical and rehabilitation techniques, meniscal repair may impact muscle recovery when performed in conjunction with ACL reconstruction. The objective of this study was to explore if meniscal repairs in the context of ACL reconstruction affected muscle recovery compared to isolated ACL reconstruction. Methods: Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Indeed, Yosmaoglu et al found a benefit of saving the gracilis (using a quadruple ST technique for ACL-Rc) at low angular velocity (60 deg/s), and the deficit was still of 9%. Also, the significant difference in terms of meniscal repair rate in both groups is not a problem, as it does not affect muscle strength after ACL-Rc, as described by Mesnard et al 42 To avoid this strength deficiency in flexion, we could opt for bone–patellar tendon–bone autograft. However, this would expose us to a greater deficit in quadriceps strength and to morbidity at the donor site, which has already been described.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Yosmaoglu et al found a benefit of saving the gracilis (using a quadruple ST technique for ACL-Rc) at low angular velocity (60 deg/s), and the deficit was still of 9%. Also, the significant difference in terms of meniscal repair rate in both groups is not a problem, as it does not affect muscle strength after ACL-Rc, as described by Mesnard et al 42 To avoid this strength deficiency in flexion, we could opt for bone–patellar tendon–bone autograft. However, this would expose us to a greater deficit in quadriceps strength and to morbidity at the donor site, which has already been described.…”
Section: Discussionmentioning
confidence: 99%
“…The varying sample size raise concerns about the risk of bias arising from smaller samples. Confounding factors, such as concomitant meniscal injuries [ 51 ] were not addressed in the statistical analysis which could have affected the investigation of the recovery of knee flexor strength. Lastly, there existed a notable risk of bias in both the non-randomized studies and the randomized controlled trials, contributing to a very low certainty of evidence based on the GRADE assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Meniscus repair usually results in further limitation of knee flexion angle and reduced weight-bearing capacity. In addition, meniscus repair surgery has certain trauma, which makes later ACL rehabilitation difficult [9]. From the perspective of joint range of motion, the peak flexion and extension torques were examined six months after ACLR surgery by Wenning et al They found that patients who underwent ACLR surgery and meniscus surgery have no significant differences from those who underwent isolated ACLR.…”
Section: Stable Ramp Lesionsmentioning
confidence: 99%
“…Therefore, surgeons should realize that repairing stable ramp lesions is not absolutely necessary and will not affect the speed of the recovery process in clinical practice. Meniscus repair should be used as a standard of care for meniscus lesions accompanying ACLR [9].…”
Section: Stable Ramp Lesionsmentioning
confidence: 99%